Painful Stimulation and Transient Blocking of Nerve Transduction Due to Local Anesthesia Evoke Perceptual Distortions of the Face in Healthy Volunteers - Skyt, Ina; Dagsdóttir, Lilja; Vase, Lene; Baad-Hansen, Lene; Castrillon, Eduardo; Roepstorff, Andreas; Jensen, Troels Staehelin; Svensson, Peter (The journal of pain, 2015)
Abstract Anecdotally, orofacial pain patients sometimes report that the painful face area feels “swollen.” Because there are no clinical signs of swelling, such illusions may represent perceptual distortions. In this study, we examine whether nociceptive stimulation can lead to perceptual distortion of the face in a way similar to that of local anesthesia. Sixteen healthy participants received injections of .4 mL hypertonic saline to induce short-term nociceptive stimulation, .4 mL mepivacaine (local anesthetic) to transiently block nerve transduction, and .4 mL isotonic saline as a control condition. Injections were administered in both the infraorbital and the mental nerve regions. Perceptual distortions were conceptualized as perceived changes in magnitude of the injected areas and the lips, and they were measured using 1) a verbal subjective rating scale and 2) a warping procedure. Prior to the study, participants filled in several psychological questionnaires. This study shows that both nociceptive stimulation ( P  < .05) and transient blocking of nerve transduction ( P  < .05) can lead to perceptual distortion of the face. A test-retest experiment including 9 new healthy subjects supported the results. Perceptual distortions were positively correlated with the psychological variable of dissociation in several conditions ( P  < .05). Perceptual distortions may therefore be influenced by somatosensory changes and psychological mechanisms. Perspective Knowledge of the factors that influence the perception of the face is important to understand the possible implications of perceptual distortions in orofacial pain disorders (and possibly other chronic pain states). Such information may ultimately open up new avenues of treatment for persistent orofacial pain.